Differential Environmental Regulation: Effects on Electric Utility Capital Turnover and Emissions - Nelson, Randy A.; Tietenberg, Tom; Donihue, Michael R. (The Review of Economics and Statistics, 1993)
This paper tests the hypothesis that differential regulations reduced the rate of capital turnover in the electric utility industry, resulting in increased emissions of sulfur dioxide. Based on a sample of forty-four privately owned electric utilities operating over the period 1969-83, the authors' results indicate that (1) regulation increased the age of capital by an average of 3.29 years (24.6 percent); (2) increases in the age of capital have no statistically significant impact on emissions; and (3) in the absence of regulation, emissions would have increased by 3.79 tons per million kWhs (34.6 percent). Copyright 1993 by MIT Press.